The Role of the Indonesian Navy in Responding to Changes in the Maritime Boundary between Timor Leste and Australia in 2018 to the status of Indonesia's Maritime Territory in order to Maintain Defense and Security Country - Harumbintoro, Nioko Budi Legowo; DAW, Martinus (Universitas Pamulang, 2024)
After the ratification of the Treaty Between Australia and the Democratic Republic of Timor Leste Establishing Their Maritime Bunderies in the Timor Sea on 31 May 2018, it marked the settlement of the maritime boundary dispute between the Democratic Republic of Timor Leste (RDTL) and Australia through the mechanism of the International Court of Arbitration in The Hague. The settlement of this maritime boundary dispute does not include Indonesia as a country that directly borders RDTL and Australia. The settlement of this maritime boundary dispute ignores the maritime boundary agreement between Indonesia and Australia in 1971 and 1972. RDTL and Australia ignore the agreement, resulting in duplication and contradiction. This study uses a qualitative method with a defense science and legal approach. The results of this study indicate that the maritime boundary agreement between RDTL and Australia is not in accordance with the provisions of international maritime law UNCLOS 1982. The drawing of maritime boundaries using meridian lines causes the sea boundaries to widen to the east and west. The Greater Sunrise area is mostly included in the RDTL sea area. This agreement is very detrimental to Indonesia in the fields of politics, economy, security and defense. In order to maintain the security and integrity of the national jurisdictional sea area, the Indonesian Navy continues to increase its Diplomatic, Police and Defense roles based on the 1971 and 1972 maritime boundary agreements and using the maritime map issued by Indonesia in 2017. The Indonesian government must be proactive in renegotiating with RDTL and Australia in accordance with the provisions of UNCLOS 1982, the 1933 Montevideo Convention and the 1961 Vienna Convention.